Computational fluid dynamic simulation of pressure perturbations generation for gas pipelines leakage. (22nd September 2015) - Liu, Cuiwei; Li, Yuxing; Meng, Lingya; Wang, Wuchang; Zhao, Fangsheng; Fu, Juntao
Highlights: The leakage occurring process is portrayed in details by the simulation of valve opening. An acoustic pressure perturbation is generated, acquired and signal-processed. The laws of pressure perturbations changing with many factors can be obtained. The attenuation law of pressure perturbations follows the exponential damping law. CFD simulation is an efficient way to carry out research on the acoustic leak detection method. Abstract: A computational fluid dynamic (CFD) simulation research on the pressure perturbations generation is accomplished and verified by experiments to study the fundamental of acoustic leak detection and location method for natural gas pipelines. When leakage occurs, gas flows out of the pipeline, and the flow field, the sound field are obtained by the established CFD simulation model. And the simulation analyses of pressure perturbations are verified by the experiments. Then, the simulation method is compared with the experimental one under variable conditions to find out the laws of pressure perturbations. Finally, the experimental demonstration of the leak location based on the pressure perturbations and the pressure perturbations attenuation are given. The results indicate that the main reason of pressure perturbations generation for natural gas pipelines is the sonic source fluctuations which are induced by turbulent fluctuations. Conclusions can be drawn that CFD simulation on the acoustic leak detection and location method for natural gas pipelines is an efficient way to carry out research and provide theoretical basis for its application.